Design and optimization of coupled microring resonators (MRRs) in silicon-on-insulator - Mulyanti, Budi; Susthitha Menon, P.; Sahbudin Shaari,; Hariyadi, T.; Hasanah, L.; Hazura Haroon,; Abang Annuar Ehsan,; Mahmudin, D.; Wiranto, G.; Majlis, B.Y. (Universiti Kebangsaan Malaysia, 2014)
The design of microring resonators (MRRs) for serial configuration, integrated in the lateral scheme was presented and simulated using 3D electromagnetic simulator based on finite integration technique. The device model is embedded on the high index contrast (HIC) structure of silicon-on-insulator with monomodal cavity for TE-mode polarizations. From the proposed model, we varied the MRRs order, waveguides separation distance and ring radius, in order to evaluate the influence of those parameters on the device performance in terms of loss, free spectral range (FSR) and quality factor (Q-factor). Upon varying the gap distances, it was found that the highest Q-factor value of the proposed design was 1275 obtained at gap separation of 150 nm for ring radius of 6 μm, while the largest FSR was 24 nm. The trade-offs between device compactness, optical bandwidth and Q-factor are also presented.